Effect of Care of Hemophiliacs in Nan Province under Limited Resources in Universal Coverage Scheme - Suriyathai, Jurarat; Techasena, Waraporn; Inta, Tanawan (Journal of Health Science of Thailand, 2017)
The purpose of this descriptive research was to evaluate care of hemophiliacs in Nan province under pre-designated resources of universal coverage scheme for purposively selected samples of 13 hemophilia patients recruited from Nan hospital between November 2007 and November 2008. Data collection was conducted using outcome measurement form. Data analysis was performed using descriptive statistics. The findings revealed that after participation in care of hemophilias Nan province under limited resources of universal coverage scheme the mean score of education for hemophilia was improved 26.83 percent. Functional Independence Score for Hemophilia was improved 3.50 percent with moderate quality of life. Cost of hemophilia treatment was reduced 44.48 percent with short hospitalization. All of hemophiliacs in Nan province had been registered and received factor VIII concentrate. Satisfaction level of clients were 95.50 percent. Satisfaction level of care providers were 95.50 percent. The mean score of ER visited from hemophiliacs was 1.25 per month. No complications emerged from administering of factor VIII concentrate and blood component. The care of hemophilia Nan province was effective for hemophilia and can be used in hospital under limited resources of universal coverage scheme.